2018
DOI: 10.1371/journal.pone.0205788
|View full text |Cite
|
Sign up to set email alerts
|

Variations of the lung microbiome and immune response in mechanically ventilated surgical patients

Abstract: Mechanically ventilated surgical patients have a variety of bacterial flora that are often undetectable by traditional culture methods. The source of infection in many of these patients remains unclear. To address this clinical problem, the microbiome profile and host inflammatory response in bronchoalveolar lavage samples from the surgical intensive care unit were examined relative to clinical pathology diagnoses. The hypothesis was tested that clinical diagnosis of respiratory tract flora were similar to cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…For example, the TT genotype at IL-1B-31 has been showed to increase the risk of chronic HBV infection. 51 Our haplotype analysis of T-31C and C3954T SNPs showed that the frequency of TC haplotype was lower in cases than in controls, which indicate that TC haplotype might reduce the risk of H. pylori infection among Jordanian population. More studies are required to confirm the present findings.…”
Section: Discussionmentioning
confidence: 66%
“…For example, the TT genotype at IL-1B-31 has been showed to increase the risk of chronic HBV infection. 51 Our haplotype analysis of T-31C and C3954T SNPs showed that the frequency of TC haplotype was lower in cases than in controls, which indicate that TC haplotype might reduce the risk of H. pylori infection among Jordanian population. More studies are required to confirm the present findings.…”
Section: Discussionmentioning
confidence: 66%
“…A similar study to ours by Huebinger et al took samples from a small group of patients in a surgical ICU, so the need for ventilation in this cohort was mainly attributed to traumatic injury. It is reasonable to assume that the common microbiome identified here may be similar to that of a healthy individual, and they were unable to determine the effects of antibiotics on the lung microbiome profile [36].…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies have reported that lung microbiota undergoes a profound reduction in the diversity of species in all MV patients [15][16][17]. To date, most of the studies refer to MV patients as a whole, with no distinction on the reasons that lead to intubation (i.e., pulmonary or non-pulmonary conditions) [17][18][19]. However, this distinction could be important, especially when analyzing the dynamics of pulmonary microbiota and the potential association with MV-related events such as ventilator-associated pneumonia (VAP).…”
Section: Introductionmentioning
confidence: 99%